ANALISIS PENGARUH LEVERAGE, PROFITABILITAS, SUKU BUNGA, JUMLAH UANG BEREDAR DAN KURS TERHADAP IHSG - Agrianti Komalasari; Husni Bagus Kananda; Chara Pratami Tidespania Tubarad (Jurnal Akuntansi dan Keuangan (JAK), 2020)
This study aims to determine the effect of leverage, profitability, interest rate, money supply, exchange rate against JCI using study case in minning company listed in Indonesia Stock Exchange (IDX) in the period 2013 until 2018. This study is done because seing that there is many factors affecting stock price at the IDX and wants to prove this factors empirically. This study is tested using classic assumption test and hypothesis test. The result shows that leverage, profitability, money supply, exchange rate has a positive effect on IHSG. Interest rate has a negative effect on IHSG.